The sustainable design book - Proctor, Rebecca (Laurence King Publishing, 2015)
"The sustainable design book features the most exciting new products in the field of green design, including materials, furniture, lighting, home accessories and personal accessories. Q&As with leading designers give insight into trends and key techniques used within the industry. Handy icons highlight each product's sustainability credentials, and web addresses of designers and retailers make each product easy to source." -- Provided by publisher